The secret of the underground room - Bellairs, John. (New York : Puffin Books, 1992)
When Father Higgins disappears, Johnny Dixon and Professor Childermass discover disturbing clues which lead them to England and an encounter with a long-dead knight.
"First published in the United States of America by Dial books for Young Readers"--Verso t.p.
Booklist.
Kirkus Review.
School Library Journal.
5.9.
5.9
Keywords: Knights and knighthood -- Fiction; Mystery and detective stories; Knights and knighthood -- Fiction; Mystery fiction; England -- Fiction; England -- Fiction